2023
DOI: 10.1101/2023.04.20.537643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Selected Coffee Constituents on Mitochon-Drial Dysfunction In An Early Alzheimer Disease Cell Model

Abstract: Alzheimer disease (AD) is an emerging medical problem worldwide without any cure yet. By 2050, more than 152 million people will be affected. AD is characterized by mitochondrial dys-function (MD) and increased amyloid beta (Aβ) levels. Coffee is one of the most commonly consumed beverages. It has many bioactive and neuroprotective ingredients of which caffeine (Cof), kahweohl (KW) and cafestol (CF) shows a variety of pharmacological properties such as anti-inflammatory and neuroprotective effects. Effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Deficits are also evident in AD, in which Mg and Fol levels are found to be reduced in brain tissues of patients [ 49 , 50 , 51 , 52 ]. In our studies using SH-SY5Y-APP 695 cells as an AD model, no increase in ATP levels was observed from the single administration of MgOr and Fol [ 26 ] The combination of the three coffee ingredients (Cof, KW, and CF) increased ATP levels [ 25 ], but Cof as single compound had no effect on ATP levels as shown in our experiments. However, it has been described in the literature that Cof affects ATP levels in HepG2 cells and smooth muscle cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Deficits are also evident in AD, in which Mg and Fol levels are found to be reduced in brain tissues of patients [ 49 , 50 , 51 , 52 ]. In our studies using SH-SY5Y-APP 695 cells as an AD model, no increase in ATP levels was observed from the single administration of MgOr and Fol [ 26 ] The combination of the three coffee ingredients (Cof, KW, and CF) increased ATP levels [ 25 ], but Cof as single compound had no effect on ATP levels as shown in our experiments. However, it has been described in the literature that Cof affects ATP levels in HepG2 cells and smooth muscle cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, it increases the activities of CAT, SOD, GRX and GPX, and cytoprotective effects of hesperetin against Aβ-induced impairment of glucose transport have been reported [ 24 ]. We recently have shown that HstP reduces ROS levels in SH-SY5Y-APP 695 cells without affecting mitochondrial function or Aβ 1–40 level [ 25 ]. In another study, we showed that magnesium-orotate (MgOr) and folic acid (Fol) reduced Aβ, soluble alpha APP (sAPPα) and lactate levels in SH-SY5Y-APP 695 cells [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All substances improve the symptoms triggered by AD in different areas of AD. HstP improves mitochondrial dysfunction [42], MgOr and Fol reduce Aβ levels within cells [43] and caffeine, kahwol and cafestol (KCC) affects glycolysis [44]. In this study, we asked ourselves whether a combination of all substances leads to an improvement in all three areas of AD.…”
Section: Introductionmentioning
confidence: 99%